Morfosintassi, semantica, concettualizzazione: costanti e varianti nell’uso dell’articolo definito - Acquaviva, Paolo (Verbum – Analecta Neolatina, 2025)
The definite article is traditionally identified with the linguistic expression of a definite description. In grammatical systems akin to those of Western European languages, the only variation would lie in the presence or absence of the article in generics (water / l’acqua). This simplistic approach has sidelined a whole range of alternative uses of the article, known but kept aside as irrelevant. This study systematically overviews this variation space. The reading as definite description or generic is its core, where variation is driven deterministically by the nominal’s denotation and by the morphosyntax of the relevant language. But the function of uniquely identifying the referent in the pragmatic and encyclopaedic context underlies more uses of the article. They outline a broader variation space, which seems arbitrary only because the relevant factors are not just strictly grammatical but also communicative.